Determination of antioxidant capacities of phlomis pungens willd. var. hispida hub.-mor - Keser, Serhat; Turkoglu, Semra; Celik, Sait; Turkoglu, Ismail (Chemical Publishing Co., 2012)
The genus Phlomis L. belongs to the Lamiaceae family and encompasses 100 species native to Turkey, North Africa, Europe and Asia. It is a popular herbal tea enjoyed for its taste and aroma. Phlomis species are used to treat various conditions such as diabetes, gastric ulcer, hemorrhoids, inflammation and wounds. In this study, ethanol and water extracts were prepared from powdered P. pungens flowers and leaves. Antioxidant activities were measured by 2,2-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS• +) radical scavenging, 1,1- diphenyl-2-picryl-hydrazyl free radical (DPPH •) scavenging, superoxide anion (O2 •) radical scavenging, reducing activity and ferrous metal chelating activity assays. In conclusion, P. pungens flowers and leaves had effective ABTS• + and DPPH• radical scavenging, superoxide anion radical scavenging, reducing power and metal chelating activities when compared with BHA, BHT and a-tocopherol as reference antioxidants.
Keywords: Antioxidant capacity; Phlomis pungens; Superoxide radical